2018
DOI: 10.1155/2018/3407306
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on the Cardiovascular System

Abstract: Obesity is a growing health problem worldwide. It is associated with an increased cardiovascular risk on the one hand of obesity itself and on the other hand of associated medical conditions (hypertension, diabetes, insulin resistance, and sleep apnoea syndrome). Obesity has an important role in atherosclerosis and coronary artery disease. Obesity leads to structural and functional changes of the heart, which causes heart failure. The altered myocardial structure increases the risk of atrial fibrillation and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
282
3
25

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(321 citation statements)
references
References 119 publications
(118 reference statements)
11
282
3
25
Order By: Relevance
“…Interestingly, we found that BMI was significantly associated with TTFM, in agreement with findings showing that high BMI or obesity is associated with coronary endothelial dysfunction, an early stage of coronary atherosclerosis that may involve the epicardial and/or resistance vessels [40,41]. The negative effects of obesity on coronary circulation include immediate changes in coronary arterial vasomotor responsiveness and the development of occlusive coronary artery disease [42,43], as well as the generation of adipocyte-derived adipokines [44,45]. Several diseases in obese patients caused by coronary microvascular inflammation have been associated with cellular mechanisms that control the secretion of adipokines and proinflammatory cytokines from adipose tissue [46].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, we found that BMI was significantly associated with TTFM, in agreement with findings showing that high BMI or obesity is associated with coronary endothelial dysfunction, an early stage of coronary atherosclerosis that may involve the epicardial and/or resistance vessels [40,41]. The negative effects of obesity on coronary circulation include immediate changes in coronary arterial vasomotor responsiveness and the development of occlusive coronary artery disease [42,43], as well as the generation of adipocyte-derived adipokines [44,45]. Several diseases in obese patients caused by coronary microvascular inflammation have been associated with cellular mechanisms that control the secretion of adipokines and proinflammatory cytokines from adipose tissue [46].…”
Section: Discussionsupporting
confidence: 90%
“…Obesity is a heterogeneous condition and, when located within the abdominal cavity, becomes an independent determinant for cardiometabolic disease causing or exacerbating other cardiovascular and metabolic risk factors, such as dyslipidemia, hypertension, insulin-resistance, and T2DM [47][48][49]. Apart from metabolic and hemodynamic alterations, central obesity is characterized by a chronic low grade inflammation and systemic oxidative stress that eventually damages the endothelium causing the loss of the endothelium antithrombotic properties.…”
Section: Platelet Alterations In Central Obesitymentioning
confidence: 99%
“…Indeed, the obesity prevalence among European adolescents reached 14.5% in 2017 while among US adolescents reached 20.6% in 2016. Obesity is linked to several comorbidities, spanning from psychological, to mechanical and most particularly to metabolic disorders, leading to female and male gonadal dysfunction in addition to the well‐recognized increased risk for type 2 diabetes mellitus, dyslipidaemia, hypertension, cardiovascular disorders, and even some types of cancer . Moreover, as the number of children and young adults with obesity steadily increases, so does the prevalence of silent consequences resulting from the chronic metabolic imbalance, which will eventually lead to serious negative health impacts in the near future .…”
Section: Introductionmentioning
confidence: 99%